2006
DOI: 10.1177/0269215506070701
|View full text |Cite
|
Sign up to set email alerts
|

Task-oriented progressive resistance strength training improves muscle strength and functional performance in individuals with stroke

Abstract: The task-oriented progressive resistance strength training programme could improve lower extremity muscle strength in individuals with chronic stroke and could carry over into improvement in functional abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
175
1
18

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(201 citation statements)
references
References 25 publications
7
175
1
18
Order By: Relevance
“…However, several researchers have described implementation of circuit class therapy with a one staff member to one participant ratio (Salbach et al, 2004;Yang et al, 2006;Rose et al, 2010). In these cases participants rotated through a program of progressive, task-specific exercises, but rather than performing the exercises independently or under distant supervision, participants were under the constant supervision of a therapist.…”
Section: Does Include Variety In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…However, several researchers have described implementation of circuit class therapy with a one staff member to one participant ratio (Salbach et al, 2004;Yang et al, 2006;Rose et al, 2010). In these cases participants rotated through a program of progressive, task-specific exercises, but rather than performing the exercises independently or under distant supervision, participants were under the constant supervision of a therapist.…”
Section: Does Include Variety In Practicementioning
confidence: 99%
“…In total nine trials were included in these two reviews (Salbach et al, 2004;Pang et al, 2005;Marigold et al, 2006;Pang et al, 2006;Yang et al, 2006;Mead et al, 2007;Mudge et al, 2009). One trial was reported in two papers (Pang et al, 2005;Pang et al, 2006).…”
Section: What Is the Evidence For The Effectiveness Of Circuit Class mentioning
confidence: 99%
“…The effects of muscular power reinforcement and gait function improvement by task-oriented training and combined functional training, which comprehensively and inclusively executes muscle strength training, postural balance training, and gait training, have been investigated by randomized-controlled trials [8][9][10][11][12][13] , and the beneficial effects of the training on gait function and gait-related ADL have been confirmed 14,15) . Most of these studies were performed to explore the effects of exercise intervention with a frequency of three times or more per week for 4-10 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Passive, energy-dissipating actuators have the advantages of inherent safety while still providing powerful force-coordination training [177,230,84,53,138,145,234,1,100,108]. With active, energy-providing actuators, assist-as-needed can be given [168,107,31,24,231], movement disorders quantified [217,47,153], and more realistic virtual environments created [86,143,194].…”
Section: -How Do the New Devices Improve Upon Existing Designs?mentioning
confidence: 99%
“…Other groups of intervention with support in literature with less focus on activities of daily living are the targeted movement-coordination training [108], progressive resistance strength training, and force-coordination training [177,230,84,53,138,145,234,1,100]. Yet, on the latter two approaches, the evidence is not conclusive [14].…”
Section: Introductionmentioning
confidence: 99%